Application of design methods on technology lessons - Нevko, Igor Vasilievich (Journal of Education, Health and Sport, 2015)
The article analyzes the scientific and pedagogical literature on the problem of using project methods in technology lessons, and determines the positive impact on improving the quality of education. It was determined that the activity of the teacher in the conditions of technological education should be clearly structured and planned. Since the lesson is not only a form of organization of teaching and educational activities in the form of cooperation between the teacher and students, but also the creative work of the teacher.